Foreclosing Infrastructure: On Permit Time and the Permission to Transit From Fossil to Renewable Fuels - Marie Widengård (Tecnoscienza)
Building on research on the time and temporality of infrastructure and climate, this article focuses on permit time, or the environmental permit as a temporal form of control. Based on an analysis of three environmental permit procedures in Sweden related to the fuel transition, the article argues that the permit can be seen as a process and device for managing and synchronising different times and temporal standpoints. Permits often lead to conflict and protests among various other stakeholders, involving temporal controversies, negotiations and compromises on infrastructure and climate futures. Permit processes therefore offer a fruitful means of studying the making of timescapes, as permits have often been issued on a continuous basis, but climate timelines and carbon rhythms may be changing this situation. Uncertain futures and the “carbon timeprint” of infrastructure may explain why Swedish courts are turning towards time-limited permits.